ANALISIS INTERRELATIONSHIP ANTARA IPM DAN POLUSI LINGKUNGAN DI INDONESIA - Dwita Tri Rezeki; Fitrah Sari Islami (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
HDI (Human Development Index) shows the quality of a society and success in social and economic development. However, as development progresses, concerns arise about the exploitation of energy use and eventually raise various environmental problems, one of which is the excess of carbon dioxide gas in the air. Therefore, this study aims to determine the causality relationship between HDI (Human Development Index) and environmental pollution in Indonesia as measured by variable carbon dioxide emissions and energy use in 1990-2020. The study used time series data and tested Vector Autoregression using the Eviews ten app. Var test results showed no causality between HDI (Human Development Index) and energy use and carbon dioxide emissions. However, in the long term, HDI is predicted to impact environmental pollution, especially air pollution. This means that the increasing quality of human resources and development does not guarantee that environmental pollution will be reduced. Then we need sustainable development